Virtual Machine Migration and Placement Schemes-limitations and challenges - Chashoo, Saima Fayaz; Malhotra, Deepti (International Journal of Computer Sciences and Engineering, 2025)
Cloud-Computing refers to the technology that provides different services as per demand via different web-based tools. Cloud computing can be thought of as a pool of resources that delivers software, data, storage, servers, computing resources etc as a service. Virtualization is a technology that acts as a ground for cloud-computing. Virtualization is a technique that enables the division of devices or resources such as servers, operating devices, memory into multiple instances and each one behaves as a whole single machine independent of each other (called virtual machine). Virtualization creates these virtual versions of devices and resources with the help of a middleware. The machine on which a middleware runs one or more virtual machines (VM) is called the Host Machine. In the life cycle of a virtual machine there may exist a necessity to transfer a virtual machine from one host machine to another host machine due to different reasons like fault tolerance, load balancing, energy management, system-maintenance etc. and this is called virtual machine migration. The two main techniques of migrating a VM between different hosts are pre-copy and post copy. In virtual machine migration, the placement of virtual machine between hosts play a critical role as it puts a straight effect on the performance, power consumption and application of resources of the physical machine on which VM is placed. This research paper provides the survey and analyses of existing techniques of virtual machine migration and also throws some light on virtual machine placement schemes. Different virtual machine migration techniques are also compared in the paper. Finally, the proposed work and conclusion are highlighted.